Characterization of MiFUT11 from Mangifera indica L.: A functional core α1, 3-fucosyltransferase potentially involved in the biosynthesis of immunogenic carbohydrates in mango fruit. (September 2019) - Okada, Takahiro; Ihara, Hideyuki; Ikeda, Yoshitaka
Abstract: In higher plants, asparagine-linked oligosaccharides ( N -glycans) in glycoproteins carry unique carbohydrate epitopes, namely, a core α1, 3-fucose and/or a β1, 2-xylose, which are common determinants responsible for the cross-reactivity of plant glycoproteins due to their strong immunogenicity. While these determinants and the relevant genes have been well characterized for herbaceous plants, information concerning whether many food plants cross-react with airborne pollens is not available. In this paper, we report on the characterization of a novel core α1, 3-fucosyltransferase gene identified from Mangifera indica L., one of the major plants potentially related to food allergy. Based on sequence information of plant homologues, we amplified a candidate cDNA ( MiFUT11 ) from pericarp tissue. An in vitro assay demonstrated that the recombinant MiFUT11 protein transfers a fucose unit onto both non-fucosylated and core α1, 6-fucosylated oligosaccharides. A glycoform analysis using MALDI-TOF mass spectrometry showed that the introduction of the MiFUT11 cDNA increased the production of a core α1, 3- and α1, 6-fucosylated pauci-mannosidic oligosaccharide in Spodoptera Sf21 cells. Our findings suggest that MiFUT11 is a functional core α1, 3-fucosyltransferase gene that is involved in the assembly of cross-reactive N -glycans in mango fruit. Graphical abstract: Image 1 Highlights: A core α1.3-fucosyltransferase cDNA from the Irwin mango fruit was characterized. The protein encoded by MiFUT11 was heterologously expressed by using an insect cell system. The MiFUT11 acts on bi-antennary oligosaccharides, irrespective of whether a core α1, 6-fucose residue is present or absent. The MiFUT11 is capable of mediating the in vivo assembly of core α1, 3-fucosylated N -glycans.